Mecanismos de governança corporativa conferem resiliência organizacional? Evidências de organizações cooperativas agropecuárias - Americo, Jean Carlos da Silva (2022)
In recent decades, unexpected events around the world have been regularly observed, causing significant impacts on organizations. These transformations highlight the need for organizations to adapt to increasingly frequent changes. This capacity of the organization is known as organizational resilience and emerges as an alternative for organizations to deal with unpredictable events. Among the various forms of business, it appears that cooperative organizations are more resilient in times of crisis and uncertainty compared to other organizations. However, cooperatives’ survival is by no means guaranteed, as this model is complex and presents ambiguous objectives. In this aspect, this thesis focuses on the relationship between organizational resilience and corporate governance, specifically, the resilience of cooperative organizations is discussed. The objective of this study is to analyze the relationship between corporate governance mechanisms and organizational resilience in agricultural cooperatives. In general terms and for methodological purposes, it is understood that cooperatives that are going (or went) through a liquidation process are those that were not resilient, either in the face of some external turbulence or in the face of failures in their internal management or governance processes. To do so, this research was conducted in three stages. The first stage identified literature contributions to organizational resilience and corporate governance in cooperative organizations, with the aim of proposing a structural model. The second stage examined the governance mechanisms adopted by continued and discontinued cooperatives through multiple case studies. And the third was a survey and qualitative comparative analysis (QCA), which verified the causal conditions of governance mechanisms adopted by continued and discontinued cooperatives. Both methodological approaches point out that participation of members in assemblies and qualification of the audit committee are factors related to the resilience of agricultural cooperatives. Participation in assemblies, preparation and publication of technical reports, cooperative education, as well as the qualification of the members of the Supervisory Board are assumptions of the structural model confirmed by case studies. The separation between ownership and control is partially confirmed, both by case studies and by qualitative comparative analysis (QCA). Furthermore, it is clear that organizational resilience occurs from a joint action of factors, with no single causal variable, sustaining the complexity of the phenomenon.